PENDAMPINGAN PELUANG KEWIRAUSAHAAN PADA MASYARAKAT DUSUN SEKINYAK DALAM BIDANG PARIWISATA - Veneranda Rini Hapsari; Usman Usman; Angelus Ewid (Jurnal Pengabdian Masyarakat Khatulistiwa, 2020)
This assistance was carried out in the Sekinyak hamlet, Belimbing Village, Lumar District, with the aim of helping the community in the hamlet to understand the importance of entrepreneurial opportunities amidst the tourism potential in the area. Even though the community already has a livelihood as a farmer, this business opportunity can add income and be a side business. This assistance is aimed at the hamlet community. The results to be achieved by the servants is the Sekinyak hamlet community has an understanding of entrepreneurial opportunities in the midst of tourism potential in the area, so as to increase income and spur creativity in doing entrepreneurship.Keywords: assistance, entrepreneurial opportunities, tourism.